Carbon Nanotube–CoF2 Multifunctional Cathode for Lithium Ion Batteries: Effect of Electrolyte on Cycle Stability. Issue 38 (30th July 2015) - Wang, Xinran; Gu, Wentian; Lee, Jung Tae; Nitta, Naoki; Benson, Jim; Magasinski, Alexandre; Schauer, Mark W.; Yushin, Gleb
<x xml:space="preserve">Abstract</x> Transition metal fluorides (MFx) offer remarkably high theoretical energy density. However, the low cycling stability, low electrical and ionic conductivity of metal fluorides have severely limited their applications as conversion‐type cathode materials for lithium ion batteries. Here, a scalable and low‐cost strategy is reported on the fabrication of multifunctional cobalt fluoride/carbon nanotube nonwoven fabric nanocomposite, which demonstrates a combination of high capacity (near‐theoretical, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgkfpz22ps" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />550mAhgCoF2−1</alternatives>) and excellent mechanical properties. Its strength and modulus of toughness exceed that of many aluminum alloys, cast iron, and other structural materials, fulfilling the use of MFx‐based materials in batteries with load‐bearing capabilities. In the course of this study, cathode dissolution in conventional electrolytes has been discovered as the main reason that leads to the rapid growth of the solid electrolyte interphase layer and attributes to rapid cell degradation. And such largely overlooked degradation mechanism is overcome by utilizing electrolyte comprising a fluorinated solvent, which forms a protective ionically conductive layer on the cathode and anode surfaces. With this approach, 93% capacity retention is achieved after 200 cycles at the current density of 100 mA g−1 and over 50% after 10 000 cycles at the current density of 1000 mA g−1.